Implementation of Corporate Social Responsibility (CSR) and the Response of the Surrounding Community from the Perspective of Islamic Business Ethics (Case Study of PT. OKI PULP & PAPER MILLS Palembang) - Herman Toni; Salmia; Novriana Dewi; Mahmud Pasaribu; Karlina Rahayu (CV Edujavare Publishing, 2026)
This study aims to analyze the implementation of Corporate Social Responsibility (CSR), determine the response of the surrounding community, and review the implementation of CSR from the perspective of Islamic business ethics at PT. OKI Pulp & Paper Mills Palembang. This study uses a qualitative approach with a case study type, where data collection techniques are carried out through in-depth interviews, direct observation, and documentation, and supported by relevant literature studies. The data obtained are analyzed using qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the company's CSR implementation has been running quite well through various programs covering social, economic, and environmental aspects, and has received a positive response from the community because it provides real benefits. Viewed from the perspective of Islamic business ethics, the implementation of CSR has reflected the values ​​of trust, justice, and social concern, although it still needs to be improved to be more optimal, sustainable, and fully aligned with the principles of Islamic ethics.